Prevalence of the Modifiable Risk Factors of Cardiovascular Diseases in Young Adults of District Hyderabad Sindh Pakistan: Risk Factors of Cardiovascular Diseases in Young Adults of District Hyderabad - Shaikh, Shakil Ahmed; Memon, Salma Farukh; Shah, Hanozia; Rahu, Hajira Naila; Laghari, Keenjher Rani; Shaikh, Saima Naz; Laghari, Zulfiqar Ali; Warsi, Jamshed (Pakistan Journal of Health Sciences, 2025)
Cardiovascular diseases are the major cause of morbidity and mortality around the world. Numerous studies concluded that populations of the subcontinent are more prone to develop cardiovascular diseases including Pakistan as compared to other countries. Objective: To determine cardiovascular disease risk factors in the healthy population of the Hyderabad district, Sindh. Methods: The cross-sectional study was conducted from July 2023 to December 2023, in this study, apparently healthy young adults of not more than 40 years of age were included. A self-designed questionnaire was set for the collection of data. Blood pressure was taken using the standard method, a mercury sphygmomanometer. South Asian standards calculated BMI, and the blood sample was taken after 10 hours of fasting for lipid profile and fasting blood sugar. Collected data were analyzed by SPSS version 23.0. Results: In this study, one risk factor was found in 276 (76%) of the participants, and Obesity was found in 41 (17%) and 66 (52%) respectively in group I and group II participants. Central obesity was found to be higher in group II 92 (72%) than in group I 69 (29%). Group II participants were found to have higher blood pressure than group I 61 (48%) and 61 (26%) respectively. Conclusions: It was concluded that 3 risk factors were found higher in females, and 4 risk factors were found higher in males, thus making the male population more prone to be affected by cardiovascular diseases even at an early age.